Taxonomia e distribuição geográfica do gênero Bostrychia Montagne (Ceramiales-Rhodophyta) nos manguezais do litoral brasileiro - FONTES, Khey Albert de Azevedo (2012)
The taxonomic studies based on morphological characters do not have effective success in the separation of lineages of the genus Bostrychia, an important component of the association of epiphytic macroalgae of mangrove denominated as "Bostrychietum." The data obtained by methods in molecular biology have proved more efficient in grouping with regular relationship. Thus, the data often go beyond the traditional classification of this genus, featuring a high occurrence of reproductively incompatible haplotype although relatively close source. Considering the high morphological plasticity of their representatives in infrageneric level, this work aimed to present the taxonomy and distribution of species of Bostrychia from mangroves occurring in the Brazilian coast. The morphological and anatomical studies were based on material collected in different Brazilian coastal mangroves, and exsicates deposited in indexed national herbaria. Macroalgae samples were collected with spatule. For taxonomic survey, it was fixed in phormaldehyde solution (4%), packed in falcon tubes (50 ml). For molecular survey, it was fixed in Ethanol P. A. and small pieces of the youngest parts of the plants has been extracted. It has been packed in silica gel. The identification of taxa followed the traditional taxonomic criteria through consultation with relevant bibliography. Allied to the taxonomic studies were used as auxiliary markers in order to better understand the polymorphism found in species of Bostrychia. We identified six species of Bostrychia in mangroves of the Brazilian coast: Bostrychia calliptera (Mont.) Mont., Bostrychia montagnei Harv., Bostrychia moritziana (Sond. ex Kutz.) J. Agardh, Bostrychia pilulifera Mont., Bostrychia radicans (Mont.) Mont. in Orb. and Bostrychia tenella (J. V.Lamour.) J. Agardh. The genus Bostrychia Mont. showed a wide distribution in the mangrove areas of the Brazilian coast. Two different lineages of B. radicans were observed using molecular markers. Molecular data suggest that B. binderi Harv. should be considered as a taxonomic entity from B. tenella (J. V. Lamour.) J.Agardh.